Pathological Scenario with the Mannose-Binding Lectin in Patients with IgA Nephropathy. (10th April 2012) - Ohsawa, Isao; Ishii, Masaya; Ohi, Hiroyuki; Tomino, Yasuhiko
Abstract : A deeper understanding of the mechanism of complement activation may help to elucidate the pathogenesis of IgA nephropathy (IgAN). Traditionally, the activation of an alternative pathway (AP) has been recognized as an enhancer mechanism of glomerular damage. This paper documents contemporary information concerning the possible pathological mechanisms of the lectin pathway (LP) in the circulation and in the glomerulus. The circulating initiator of LP activation is not fully understood. However, ligands for mannose-binding lectin (MBL) which are among the starter molecules of the LP are aberrant glycosylated molecules-containing immune complex. Recent reports have focused on N -glycans on secretory IgA as a candidate ligand. Mesangial deposits of MBL are seen in 25% of patients with IgAN. Mesangial deposits of MBL and C4 and/or C4 breakdown products are implicated as markers for disease progression of IgAN. On the other hand, patients with MBL deficiency tend to show better clinical presentation and lower levels of urinary protein and serum creatinine than MBL-sufficient patients. It is now recognized that involvement of AP and LP constitutes an additional mechanism for explaining the progression of IgAN.